Collusive and adversarial replication - Adam Bouyamourn (Research & Politics)
I describe a game in which social ties between members of a research community may discourage prospective replicators from debunking papers that misreport results. Here, replication is an entrance decision, as a Replicator chooses whether or not to Replicate a given paper. A high level of social connectedness between members of a research community increases the field-wise False Discovery Rate, a measure of the social welfare associated with a healthy publication process. The moral is that larger, more diverse academic fields with fewer social ties are more likely to have an adversarial culture around replication, and that this improves social welfare. I consider three proposals to improve replication practices: Random auditing, or police-patrol replication; automated unit tests; and a recent proposal to lower the threshold for statistical significance. I argue that random auditing and automated unit tests can improve social welfare, but that the effect of lowering the statistical significance threshold is ambiguous.